The Rejectionist Ethic and the Spirit of the Green Economy: The Western Zeitgeist, the Croatian Context, and Green Entrepreneurship - Petrović, Nikola; Peternel, Lana; Ančić, Branko (Traditiones, 2020)
This article explores how particular layers of the Western Zeitgeist and the Croatian social and economic context influenced the emergence and development of green entrepreneurship, and whether they could be helpful in understanding the potential transition to a green economy. It is argued that what initially drove several of interviewees to green entrepreneurships could be subsumed under the label rejectionist ethic used here to encompass different modes of rejecting modern economic institutions and the usual life trajectory of completing one’s education and working at a job in line with one’s social position and/or education.